Imunidade humoral aos agentes da babesiose durante o segundo ano de vida de bovinos em área marginal ao vetor Boophilus microplus - Reiniger, Regina Celis Pereira (2008)
The presence of anti-Babesia bovis and anti-B. bigemina immunoglobulins (IgG class) were evaluated, by indirect fluorescent antibody test, in bovine sera from a naturally tick-infected beef cattle herd. Samples were collected from 31 heifers, from 13 to 24 months of age, from a farm located South of Rio Grande do Sul, Brazil. Blood samples were monthly collected followed by observing the presence of Boophilus microplus ticks in cattle. Climatic data were also observation. Mean temperature and relative humidity showed to be higher than their climate normal (1971-2000), allowing constant tick infestations throughout the year. Serologic tests showed that 100% of the animals remained positive for B. bigemina during the experimental period. For B. bovis, however, this condition was only reached from 17 months of age onwards, after the classical third tick generation infestation (autumn). These results showed that the enzootic stability was maintained in this farm, as observed earlier when these same animals were monitored in their first year of age. This epidemiological condition being unusual for this region. The experimental animals showed lower anti-B. bovis (P=0,0002) and anti-B. bigemina (P<0,0001) specific-immunoglobulins when compared to their first year averages. Anti-B. bigemina specific-immunoglobulins were significantly higher than anti-B. bovis specific-immunoglobulins (P=0,0001). These results reveal a situation of enzootic stability in geographical areas early described as of enzootic instability for cattle babesiosis, and provide information to better understand the high frequency of B. bovis outbreaks in this region.